2017
DOI: 10.4049/jimmunol.1601694
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Containing Exosomes Derived from Cancer Cells Treated with Topotecan Activate a STING-Dependent Pathway and Reinforce Antitumor Immunity

Abstract: Danger-associated molecular patterns derived from damaged or dying cells elicit inflammation and potentiate antitumor immune responses. In this article, we show that treatment of breast cancer cells with the antitumor agent topotecan (TPT), an inhibitor of topoisomerase I, induces danger-associated molecular pattern secretion that triggers dendritic cell (DC) activation and cytokine production. TPT administration inhibits tumor growth in tumor-bearing mice, which is accompanied by infiltration of activated DCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
205
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(207 citation statements)
references
References 57 publications
1
205
1
Order By: Relevance
“…We next examined the mechanism(s) for how SINCRO regulates IFN‐β expression. As dead cell‐derived and exosomal nucleic acids have the potential to induce type I IFN, we asked whether SINCRO induced the release of nucleic acids. To test this, we first stimulated B16F1 cells with SINCRO for 6 hours, removed the compound by washing, and then collected the medium from the cells incubated for another 6 hours.…”
Section: Resultsmentioning
confidence: 99%
“…We next examined the mechanism(s) for how SINCRO regulates IFN‐β expression. As dead cell‐derived and exosomal nucleic acids have the potential to induce type I IFN, we asked whether SINCRO induced the release of nucleic acids. To test this, we first stimulated B16F1 cells with SINCRO for 6 hours, removed the compound by washing, and then collected the medium from the cells incubated for another 6 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Short fragments of single‐stranded DNA (ssDNA), dsDNA, and RNA, as well as complete mitochondrial genome (mtDNA) have been found within EVs . While the biological function of EV‐ssDNA and EV‐dsDNA remains to be elucidated, recent study demonstrates that antitumor drug topoisomerase I inhibitor topotecan (TPT)‐treated murine breast cancer E0771 cells release EV‐encapsulated DNA to activate stimulator of interferon genes (STING)‐dependent pathway, thereby enhancing antitumor immunity for tumor suppression . Meanwhile, EV‐mtDNA was found to be horizontally transferred to CAFs to increase self‐renewal potential and subsequent restoration of the oxidative phosphorylation (OXPHOS) function of OXPHOS‐deficient breast cancer cells under hormonal therapy, leading to treatment resistance .…”
Section: Ev Biology and Cancermentioning
confidence: 99%
“…(b) DNA ‐mediated activation of STING triggers topotecan‐dependent anti‐tumor immunity against murine breast cancer cells (E0771) in vivo: Topotecan‐treated cancer cells release exosomes that contain DNA that activate DC s via cGAS ‐ STING signaling. DC activation leads to Type I IFN and cytokine production crucial for the anticancer reponse . (c) The danger signal cGAMP boosts the anti‐tumor activity of the chemotherapy 5‐Fluorouracil (5‐ FU ): In mice, the combination of 5‐ FU and cGAMP leads to tumor cell death by immunogenic cell death.…”
Section: A Renewed Interest In the Role Of Nucleic Acids As Danger Simentioning
confidence: 99%
“…However, DNase treatments fail to abrogate Sting activation upon topotecan treatment suggesting the possibility that DNA derived from topotecan‐treated E0771 cells is tightly associated with protective structures. Further investigation revealed that topotecan‐treated cancer cells release exosomes that contain DNA that activate DCs via STING signaling (Figure b) . To explore how DNA in the exosome is delivered to DCs, GM‐DCs were incubated with CSFE‐labeled exosomes purified from topotecan‐treated E0771 cell supernatant and analyzed their engulfment by FACS analysis.…”
Section: A Renewed Interest In the Role Of Nucleic Acids As Danger Simentioning
confidence: 99%
See 1 more Smart Citation